2002
DOI: 10.1097/00004714-200208000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Reboxetine, a New Noradrenaline Selective Antidepressant, Is at Least as Effective as Fluoxetine in the Treatment of Depression

Abstract: The clinical profile of reboxetine, a selective noradrenaline reuptake inhibitor, was compared with that of the selective serotonin reuptake inhibitor fluoxetine and placebo in a double-blind, multicenter, parallel-group clinical trial of patients with major depression. Among the 381 patients treated with reboxetine 8 to 10 mg/day, fluoxetine 20 to 40 mg/day, or placebo for up to 8 weeks, a statistically significant greater reduction in the mean Hamilton Rating Scale for Depression (21-item HAM-D) total score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Our results suggest the presence of strain-dependent mechanisms underlying the antidepressant response. The onset of the therapeutic effects of antidepressant drugs in patients exhibits a characteristic delay of several weeks (Andreoli et al, 2002;De Nayer et al, 2002;Blier, 2003). The traditional FST is a reliable assay with strong predictive validity for antidepressant compounds that assesses the behavioral response to acute drug treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest the presence of strain-dependent mechanisms underlying the antidepressant response. The onset of the therapeutic effects of antidepressant drugs in patients exhibits a characteristic delay of several weeks (Andreoli et al, 2002;De Nayer et al, 2002;Blier, 2003). The traditional FST is a reliable assay with strong predictive validity for antidepressant compounds that assesses the behavioral response to acute drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant proportion of nonresponsive patients (Kampf-Sherf et al, 2004), and a delay of 2-4 weeks before therapeutic efficacy is apparent (Andreoli et al, 2002;De Nayer et al, 2002;Blier, 2003) impair the treatment of depression. A better understanding of the mechanisms underlying antidepressant efficacy may permit the development of novel treatments with greater efficacy and faster onset.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and clinical observations indicated that reboxetine has high affinity and selectivity for norepinephrine (NE) transporters [17][18][19] . A review suggested that with its remarkable selectivity to NE over serotonin transporters, reboxetine is a rational alternative for patients who are resistant to conventional antidepressants, such SSRIs and TCAs 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Results from placebo-controlled trials suggest that reboxetine is significantly superior to placebo in treating major depression (Massana, 1998;Versiani et al, 1999Versiani et al, , 2000Andreoli et al, 2002). Reboxetine was also compared to imipramine (Berzewski et al, 1997), desipramine (Ban et al, 1998) and fluoxetine (Massana et al, 1999), and was found to be as effective as these comparators in treating MDD.…”
Section: Discussionmentioning
confidence: 99%